Implementasi Strategi dan Kebijakan Pendidikan Islam - Wahyuni, Sri; Anggi E.R., M. Shahid; Aprianto, Iwan; J, Jamrizal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to examine strategies for combating the potential for corruption through the implementation of anti-corruption education within educational institutions, including both schools and universities. The research adopts a qualitative approach, with data obtained from various sources such as books, academic journals, scholarly articles, and other relevant literature. The primary objective of this study is to reinforce and internalize anti-corruption values among the younger generation, particularly within formal educational settings. This initiative is driven by the persistent prevalence of corruption in Indonesia, which remains a significant national issue. Several contributing factors to corrupt behavior have been identified, including individual moral failings, familial and societal influences, economic and political conditions, and organizational weaknesses. Anti-corruption education is recognized as an effective preventive measure, which should begin by instilling ethical values and integrity from an early stage. This is especially crucial for university students, who are regarded as future leaders and bear the responsibility of upholding national development and governance standards.